Genetic Structure and Gene Flow of Moss Sanionia uncinata (Hedw.) Loeske in Maritime Antarctica and Southern-Patagonia - Hebel, Ingrid; Dacasa Rüdinger, Maria Carmen; Jaña, Ricardo A.; Bastias, Joaquin (Frontiers in Ecology and Evolution, 2018)
Bryophytes are a major component of vegetation in ice-free coastal regions of Antarctica. Sanionia uncinata (Hedw.) Loeske is distributed from northern and central Maritime Antarctica to Marguerite Bay in the southern part of this biome where it occurs sparsely. Production of sporophytes is rare for S. uncinata in Antarctica, thus a high level of genetic uniformity among populations is expected (Lewis Smith 1984). Several ice advances and retreats events in last thousands of years in Patagonia and Antarctica could have driven different processes of speciation at fine scale or triggered genetic differentiation among populations, leading to unique genetic populations. A few studies have analyzed the genetic structure of mosses in Antarctica, but none in Maritime Antarctica or in the nearby zones such as southern Patagonia. Based on Amplified Fragment Length Polymorphism (AFLP) and grouping analysis, we determined levels of intra /and inter-population genetic diversity of S. uncinata in sites of this region. The results revealed that gene diversity within populations was low and that populations did not have significant genetic differentiation. Also, no correlation was found between genetic variability and geographic distance (R2 = 0.031). However, we distinguished two groups of populations. One of them clustered populations with low values of genetic diversity. The other one was made out of populations showing much higher genetic diversity. Cluster 1 was the most geographically widely distributed covering populations from northern part of southern Patagonia to southern part of studied populations in Maritime Antarctica. Cluster 2 had the highest level of polymorphism, but spatially is very restricted to four populations in the Maritime Antarctica and southern Patagonia. We found substructures in some populations of the Maritime Antarctica such as in the Coppermine, Byers and Suffield populations. The underlying causes of this subdivision could be the asexual reproduction and significant abiotic factor affecting the presence of this moss species, but also the autoecious condition of this species. The importance of results is the concept of genetic connectivity among bioregions of South Patagonia and Antarctica suggesting additionally this interaction may have occurred repeatedly after the LGM, resulting in the vegetation that grows in Antarctica today.